Post-Cholecystectomy nutritional management: a comprehensive review of evidence-based guidelines and clinical practice - Chuang Guo; Yake Lan; Yu Zhang; Yuan Guo; Chunyan Sun; Minghui Li (Frontiers in Surgery, 2026)
Background Cholecystectomy is one of the most common abdominal surgeries worldwide, yet postoperative nutritional management remains variable. This review synthesizes current evidence on nutritional care after cholecystectomy, with a focus on actionable insights for clinicians. Methods We conducted a non-systematic narrative review of English-language literature published from January 2010 through June 2026, supplemented by manual searches of guidelines. Due to the narrative design, we did not perform a formal risk-of-bias assessment or meta-analysis. Findings Postoperative gastrointestinal symptoms (e.g., bloating, diarrhea, dyspepsia) are common, but their incidence and etiology vary widely. Early oral feeding within 24 h may reduce hospital stay. High-risk patients (diabetes, obesity, elderly) may benefit from protein supplementation (1.2–1.5 g/kg/day) and selective fat-soluble vitamin monitoring when clinically indicated. We provide a risk-stratified algorithm, critically appraise conflicting evidence, and identify knowledge gaps. While standardized ERAS protocols exist for elective cases, complicated scenarios (acute cholecystitis, post-pancreatitis) require special consideration. Conclusion This review provides an evidence-informed, cautious framework for individualized postoperative nutritional support, emphasizing that most recommendations are extrapolated from other surgical populations and require validation in cholecystectomy-specific trials.